Cross-linked hemoglobin converts endotoxically inactive pentaacyl endotoxins into a physiologically active conformation - Klaus Brandenburg and Patrick Garidel and Jörg Andrä and Gudrun Jürgens and Mareike Müller and Alfred Blume and Michel H. J. Koch and Jack Levin (The journal of biological chemistry : JBC, 2003)
The interaction of purified αα cross-linked hemoglobin (ααHb) with a pentaacylated mutant lipopolysaccharide (pLPS) and the corresponding lipid A (pLA) was studied biophysically and the effects correlated with data from biological assays, i.e. cytokine induction (tumor necrosis factor-α) in human mononuclear cells and the Limulus amebocyte lysate assay. Fourier transform infrared spectroscopic and Zeta-Sizer experiments indicated an electrostatic as well as a non-electrostatic binding of ααHb to the hydrophilic and to the hydrophobic moieties of the endotoxins with an increase of the inclination angle of the pLA backbone, with respect to the membrane surface, from 25° to more than 50°. Small angle synchrotron radiation x-ray diffraction measurements indicated a reorientation of the lipid A aggregates from a multilamellar into a cubic structure as a result of ααHb interaction. Thus, in the absence of ααHb, the molecular shape of the pentaacyl samples was cylindrical with a moderate inclination of the diglucosamine backbone, whereas, in the presence of the protein, the shape was conical, and the inclination angle was high. The cytokine-inducing capability in human mononuclear cells, negligible for the pure pentaacylated compounds, increased markedly in the presence of ααHb in a concentration-dependent manner. In the Limulus assay, the pentaacylated samples were active a priori, and their activity was enhanced following binding to ααHb, at least at the highest protein concentrations. The data can be understood in the light of a reaggregation of the endotoxins because of ααHb binding, with the endotoxin backbones then readily accessible for serum and membrane proteins. By using fluorescence resonance energy transfer spectroscopy, an uptake of the endotoxin-Hb complex into phospholipid liposomes was observed, which provides a basis for cell activation.